Resposta do cultivar de soja ’santa rosa’ a aplicação de P, K e calcário, em latossolos do Triângulo Mineiro: II - Correlação com análise química do solo - Braga, José Mário; A Rocha Ferrari, Ruy; M de Oliveira, Laede; S Sediyama, Carlos (Revista Ceres, 2025)
With data on soybean production obtained with applications of phosporus at levels of 0, 100, 200 and 300 kg of Pg0sha, with and without lime, and of potassium at levels of 0, 50 and 100 kg of Ky0/ha and results of chemical analyses of 17 latosols from the Triangulo Mineiro, correlations between soil plant parameters were determined in order to provide a better orientation for recomendations for fertilizings soybeans. The results allowed the conclusion that pH values and the sum of bases were positively related to soybean yield and to relative production according to phosphorus levels, but the opposite relationship was observed in respect to exchangeable aluminum. Correlation coefficients between available phosphorus and soybean and between available phosphorus and relative production according to phosphorus application levels were not significant. Available potassium, at the same time, correlated significantly and positively with soybean production and with response to the use of phosphorus, but the correlation between available potassium and relative production according to potassium application level was not significant.